The Interrater Reliability of Subjective Assessments of the Babinski Reflex. Issue 2 (3rd March 2016) - Dafkin, Chloe; Green, Andrew; Kerr, Samantha; Veliotes, Demetri; Olivier, Benita; McKinon, Warrick
ABSTRACT: The Babinski reflex is a clinical diagnostic tool; however, the interrater reliability of this tool is currently greatly contested. A comparison between rater groups with objective measurements of the Babinski reflex was therefore conducted. Fifteen recorded Babinski reflexes were assessed by 12 neurologists and 12 medical students as being either pathological or nonpathological. Kinematic and electromyographic variables were collected and used to assess which aspects of the Babinski reflex predict classification. Substantial interrater agreement within the neurologist and student groups (κ = .72 and .67, respectively) was shown; however, there were some differing aspects between what neurologists and students used to assess the reflex as determined by objective kinematic measurements.